Stand Volume Growth and Yield Equations for Young, Thinned Red Pine Plantations - Sadiq, Riyaz A. (Indian Forester, 1994)
Intensive management of young platations requires estimates of their growth and yield. The effect of early thinnings upon these estimates must be taken into account. The Combined variable formula to estimate stand volumes was modified to include a variable representing the degree of thinning. Three forms of volume growth models, compatible with the yield model, were derived and their accuracy and stability tested using data from 10 to 35 -year- old red pine plantations growing in southern Ontario. Prediction errors were within Â± 18.11 and Â± 9.35 per cent of the actual volume growth and yield values respectively. Implications of the forms of the model are also discussed.